Reversible cerebral vasoconstriction syndrome with associated myocardial injury: A case report - Quiroz Alvarez, Juan Esteban; Estrada Atehortua, Andrés Felipe; Arroyave Peña, Tatiana (Medicina UPB, 2023)
Reversible Cerebral Vasoconstriction Syndrome is a rare condition, and its pathophysiology is not yet fully understood. Its clinical presentation is characterized by neurological manifestations such as “thunderclap” headache, focal deficit, vomiting, photophobia, and, in severe cases, it can lead to complications such as ischemic or hemorrhagic cerebrovascular events. The diagnosis is made through cerebral angiography, CT angiography, or magnetic resonance angiography, which demonstrate vasoconstriction of the cerebral arteries with spontaneous resolution, which in most cases is consistent with a good clinical prognosis. Here, we present the case of a patient with reversible cerebral vasoconstriction syndrome and associated myocardial injury, where a diagnosis was achieved through imaging and timely treatment. The importance of this case lies in raising awareness about the early recognition of a rare myocardial complication of reversible cerebral vasoconstriction syndrome, which carries a risk of morbidity and mortality within the spectrum of cerebrovascular disorders.
Keywords: vasoconstriction; headache; hypertension; stroke